A Comparative Analysis of Building Orientation and Indoor Thermal Condition of Some Buildings in Benin City, Nigeria - Yusuf Haruna TASHOK; K.O. DIMUNA (PT Keberlanjutan Strategis Indonesia, 2025)
The study focuses attention on orientation of buildings as a significant design consideration due to its influence to improve the indoor thermal comfort. The aim of the study is to comparatively analysis the effect of building orientation on indoor thermal condition of buildings in the study area. To achieve the aim of the study, a field survey was carried out in five neighbourhoods using 550 administered questionnaires. Secondly, buildings relatively oriented longitudinally in the East-West and buildings oriented longitudinally in the North-south direction were identified for comparison in their indoor thermal condition. Thirdly, the indoor thermal condition of buildings in relation to building orientation in the study area are measured. Data obtained was analysed with the aid of analyses of variant to determine the influence of building orientation on indoor thermal condition of buildings. The result shows no significant relationship between building orientation and indoor thermal condition among the buildings assessed as the p-value equals 0.792. This result contrast most related research works, being that, most buildings were built with foreign building materials with one window in their functional spaces. No adequate building’s setbacks, high wall fence, and most buildings occupied more than 50% of the total plot size, which may have resulted in the distortion of air circulation around such buildings and increase in air temperature. The study therefore recommends a strict monitory of physical developments by relevant agency and proposed development must incorporate passive design strategies that works with the local climate to maintain a comfortable temperature indoors.